Effects of hole taper on mild steel machining using injection flushing type of electrical discharge machine - Sahwal Waty, Marno (2010)
Electric discharge machining (EDM) is a process for shaping hard metals and forming deep and complex-shaped holes by arc erosion in all kinds of electro-conductive materials. The effectiveness of EDM process with Mild Steel is evaluated in terms of the material removal rate, electrode wear rate and angle taper of the workpiece produced. The objective of this study is to study the effects of hole taper on mild steel machining using injection flushing type of EDM. Existing systems are generally used to produce, straight, parallel-walled holes, however there are certain application of the area exist taper holes and in the same time the machining performances also be considered. The problem of this project is improper flushing and electrode material would cause erratic cutting and poor machining rate or performance. For this thesis the influence of peak current, pulse on time, pulse off time and pressure flushing on EDM performance is discussed. The analysis of the influence of these factors was carried out by using full factorial experiment. The result of the experiment then was collected and analyzed by using STATISTICA Software. There are two level setting for each factor and the dielectric fluid is used is kerosene. The effects of hole taper on mild steel was analyzed and discussed.